Estimation of total carbon pools and fluxes in a selective logging forest area in Tawau, Sabah, Malaysia - Nurul Syakilah Suhaili (2023)
The tropical rainforest has a great capability for storing an enormous amount of carbon in its carbon pools and different logging methods affects the vegetation’s ability to restore carbon. There is also a growing concern that unsustainable logging methods threaten the forest ecosystem, thus triggering the release of forest carbon into the atmosphere hence contributing to ongoing climate change. This study aimed to investigate the impacts of different logging methods on the soil physicochemical properties, total ecosystem carbon pools, and the soil carbon fluxes in Gunung Rara Forest Reserve, Tawau, Sabah, Malaysia. The two logging methods that were investigated are supervised logging with climber cutting (SLCC), conventional logging (CL), and an unlogged forest, which is a primary forest (PF) that represents the control areas. The size for each plot was 0.36 ha (60 m x 60 m) and each plot was replicated four times resulting in a total of 12 plots. Forest inventory was done to measure the diameter at breast height (DBH) of the standing trees with DBH of more than 10 cm while soil sampling at four different depths (0-10 cm, 10-20 cm, 20-50 cm, and 50-100 cm) was done for soil analysis. Coarse woody debris was measured one meter along the plot boundaries and the organic layer was collected using a 0.25 m2 sampling frame. The estimation of litterfall production and the soil carbon fluxes were measured by the soil respiration rate annually, from March 2019 to February 2020. The litterfall was collected using 0.25 m2 litterfall traps while soil respiration was recorded using a Vaisala Hand-Held Carbon Dioxide Meter. Allometric equations were used to estimate the standing tree’s and root’s carbon pools. The soil samples were analyzed using a Vario Max CN Elemental Analyzer for their carbon content. After 26 years of being logged, the finding shows that there was no significant difference observed in the soil physicochemical properties, total ecosystem carbon pools, and soil carbon fluxes between the different logging methods and the primary forest. The soil in all study areas was found acidic with a range from 3.87 to 4.54 and sand dominated the soil texture with a mean value of up to 71%. The primary forest area still holds the highest total ecosystem carbon pools with 281.82 ± 23.55 Mg C ha-1. Among the logging methods, the supervised logging with climber cutting area holds a slightly higher mean value of total ecosystem carbon pools which is 268.39 ± 9.59 Mg C ha-1 compared to the conventional logging area with a mean value of 265.12 ± 14.30 Mg C ha-1. The results also showed that the standing trees and soil carbon pools contributed the most to total carbon pools with approximately 54% and 29%, respectively. On the other hand, the supervised logging with climber cutting area resulted in the highest rate of soil respiration throughout the year with a mean value of 161.75 ± 21.67 mg C m-2 h-1, followed by the primary forest area with a mean value of 149.59 ± 12.46 mg C m-2 h-1. The conventional logging area resulted in the lowest soil respiration rate with a mean value of 140.54 ± 12.54 mg C m-2 h-1. These findings highlight the importance of accurate quantification of the effect of different logging methods on the forest’s carbon pools.